Cover crops optimize soil fertility and soybean productivity in the Cerrado of MATOPIBA, Brazil - Andrada, Hosana Aguiar Freitas de; Sagrilo, Edvaldo; Oliveira Júnior, José Oscar Lustosa de; de Sousa, Daiane Conceicao; Costa, Carlos Pedro de Menezes; Costa, Paula Muñiz; Araujo Neto, Raimundo Bezerra de; Alcantara, Rosa María Cardozo Mota de; Leite, Luis Fernando Carvalho; Furtado, Mariléia Barros; Beltran, Marcelo Javier; Cafaro La Menza, Nicolás; et al. (MDPI, 2025)
The main challenge of soybean cultivation in Brazil’s last agricultural frontier is to ensure sustainable production. This study aimed to evaluate the use of cover crops (CC) to improve soil fertility, plant nutrition, and soybeans productivity grown in the Cerrado of Brazil. The study was carried out on a farm located in the state of Maranhão, Brazil, with nine treatments, fallow and CC preceding soybean cultivation: (i) Millet (Pennisetum glaucum L.); (ii) Marandu (Urochloa brizantha); (iii) Ruziziensis (Urochloa ruziziensi); (iv) Tanzania (Megathyrsus maximum); (v) Massai (Megathyrsus maximum); (vi) cowpea (Vigna unguiculata L.); (vii) pigeon pea (Cajanus cajan L.); and (viii) Crotalaria (Crotalaria juncea). An analysis for the characterization of the biomass of cover crops and fallow was carried out. Soil chemical and biological properties, soybean foliar nutrient concentrations, and the soybean seed yield and quality grown in sequence to the CC were also analyzed. Soil microbial carbon was favored by the cultivation of ‘Marandu’, ‘Ruziziensis’, ‘Tanzania’, and cowpea. Nutrient cycling promoted by CC contributed to the maintenance of soil quality and increases in the leaf nutrient concentrations of soybeans. The cultivation of millet, ‘Tanzania’, ‘Massai’, cowpea, and C. juncea increased the soybean yield. Cover crops improved soil fertility while increasing soybean productivity, thus being an effective strategy for the achievement of sustainable soybean production.